Nowhere left to go : how climate change is driving species to the ends of the earth - Von Brackel, Benjamin (The Experiment, LLC, 2022)
"Harrowing journeys of animals and plants-fleeing skyrocketing temperatures and mega-droughts-reported from the frontlines of the greatest migration of species since the Ice Age"--